Cost-benefit Analysis of Maintaining a Fully Stocked Malignant Hyperthermia Cart versus an Initial Dantrolene Treatment Dose for Maternity Units. (August 2018) - Ho, Phi T.; Carvalho, Brendan; Sun, Eric C.; Macario, Alex; Riley, Edward T.
Abstract : What We Already Know about This Topic: Prompt availability of dantrolene is important for treating malignant hyperthermia and has resulted in lowered mortality rates Maintaining a malignant hyperthermia cart and full treatment dose of dantrolene is expensive, particularly for locations with low incidence of malignant hyperthermia, such as labor-and-delivery units What This Article Tells Us That Is New: Cost-benefit analysis showed that the costs associated with maintaining a malignant hyperthermia cart with a full dantrolene supply within 10 min of a maternity unit exceeded the benefits Modeling suggested that a more cost-effective approach would be to keep just an initial dose of dantrolene on the maternity unit, with a central supply of dantrolene available within 30 min Background: The Malignant Hyperthermia Association of the United States recommends that dantrolene be available for administration within 10 min. One approach to dantrolene availability is a malignant hyperthermia cart, stocked with dantrolene, other drugs, and supplies. However, this may not be of cost benefit for maternity units, where triggering agents are rarely used. Methods: The authors performed a cost-benefit analysis of maintaining a malignant hyperthermia cart versus a malignant hyperthermia cart readily available within the hospital versus an initial dantrolene dose of 250 mg, on every maternity unit in the United States. A decision-tree model was used to estimate the expected number of lives saved, and this benefit was compared against the expected costs of the policy. Results: We found that maintaining a malignant hyperthermia cart in every maternity unit in the United States would reduce morbidity and mortality costs by $3, 304, 641 per year nationally but would cost $5, 927, 040 annually. Sensitivity analyses showed that our results were largely driven by the extremely low incidence of general anesthesia. If cesarean delivery rates in the United States remained at 32% of all births, the general anesthetic rate would have to be greater than 11% to achieve cost benefit. The only cost-effective strategy is to keep a 250-mg dose of dantrolene on the unit for starting therapy. Conclusions: It is not of cost benefit to maintain a fully stocked malignant hyperthermia cart with a full supply of dantrolene within 10 min of maternity units. We recommend that hospitals institute alternative strategies ( e.g ., maintain a small supply of dantrolene on the maternity unit for starting treatment). Abstract : Cost-benefit analysis showed that the costs associated with maintaining a malignant hyperthermia cart with a full dantrolene supply within 10 min of a maternity unit exceeded the benefits. Modeling suggested that a more cost-effective approach would be to keep just an initial dose of dantrolene on the maternity unit, with a central supply of dantrolene available within 30 min.